Optimization of Kolang-Kaling Seed Galactomannan Serum Using Response Surface Methodology - Anggraeni, Rosiana Sofia; Nurulita, Nunuk Aries; Astuti, Ika Yuni (Sultan Agung Islamic University of Semarang, 2026)
Background: Ultraviolet (UV) exposure promotes free radical formation, leading to oxidative stress, lipid peroxidation, inflammation, and hyperpigmentation. Galactomannan derived from kolang-kaling (Arenga pinnata) exhibits antioxidant activity with potential protective effects against UV-induced damage. In serum formulations, carbomer and triethanolamine (TEA) are commonly combined as gelling agents to achieve desirable physicochemical properties. Objective: This study aimed to optimize a galactomannan-based facial serum by determining the most effective Carbomer–TEA concentration combination using Response Surface Methodology (RSM). Methods: A formulation optimization study was conducted employing the RSM approach with Design Expert software to evaluate the interaction effects of Carbomer and TEA concentrations on serum characteristics. Results: The optimal formulation predicted by the model consisted of 0.100% (w/v) Carbomer and 1.047% (w/v) TEA. Conclusion: Response Surface Methodology successfully optimized the galactomannan facial serum formulation. The identified combination of Carbomer and TEA is expected to provide suitable serum properties while supporting the antioxidant potential of galactomannan against UV-induced oxidative damage.